Reformasi Penegakan Hukum Kekayaan Intelektual (Hak Merek) di Indonesia sebagai Upaya untuk Keluar dari Priority Watch List - Mu'ammar Ilyas (Jurnal Hukum Lex Generalis, 2025)
The widespread circulation of counterfeit goods and violations of intellectual property rights (IPR), particularly in trademark rights in Indonesia, reflects the weakness of the country's law enforcement system. Indonesia is currently still one of the countries listed on the Priority Watch List. This stands in stark contrast to the situation observed by the author in France, which is known for its firm and consistent IPR enforcement, including direct field actions such as the destruction of counterfeit goods in airport. This research aims to analyze the differences in the legal enforcement systems for trademark rights between Indonesia and France, in order to identify deficiencies and provide constructive recommendations for building a more efficient legal system in Indonesia. The method used is normative juridical with a comparative study approach. The findings show that France's success is supported by clear and strict regulations, public awareness, and synergy among institutions. In contrast, Indonesia faces structural legal challenges and societal cultural issues. The study concludes that legal system reform, law enforcement, and public education of IPR in Indonesia is urgently needed to promote efficient legal protection and enhance national competitiveness within the framework of economic rights in the industrial and trade sectors.